2020
DOI: 10.1111/dth.13949
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dermatologic conditions in Turkey and Italy by using Google Trends analysis in the era of the COVID ‐19 pandemic

Abstract: Many areas of life including patterns of dermatological diseases that patient attend to the hospital were tremendously affected by implementing stay‐at‐home orders during the COVID‐19 pandemic. We aimed to identify the dermatologic interest of the public during the COVID‐19 pandemic by using Google Trends. The terms “acne”, “hair loss”, “eczema”, “genital warts”, “molluscum contagiosum”, “botox”, “skin cancer”, “sunscreen” were analyzed on first April, first May, first June 2020, and the corresponding period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 26 publications
0
38
0
1
Order By: Relevance
“…Other authors have observed this with rhinoplasty as well. 2 The psychology and neurocognition literature has many experiments that elucidate just how complex our sense of ''self-perception'' really is. 3 Mirror evaluation of our own faces versus those of known friends demonstrates a strong difference in hemispheric cognition.…”
Section: From the Time Of Narcissus We Have Been Beguiled By Our Own mentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have observed this with rhinoplasty as well. 2 The psychology and neurocognition literature has many experiments that elucidate just how complex our sense of ''self-perception'' really is. 3 Mirror evaluation of our own faces versus those of known friends demonstrates a strong difference in hemispheric cognition.…”
Section: From the Time Of Narcissus We Have Been Beguiled By Our Own mentioning
confidence: 99%
“…A recent analysis of Google search trends during the pandemic showed the terms ''acne'' and ''hair loss'' are increasing in this newly virtual reality. 2 They attributed this trend to the association of acne and hair loss with anxiety and depression, common psychological conditions during quarantine. We suspect the trend may also arise from people constantly seeing themselves on video and becoming more aware of their appearance.…”
mentioning
confidence: 99%
“…was the only research where Google Trends were used, specifically, there is no research found about the effect of COVID-19 on skincare. 16 In our study we aimed to determine whether there is any significant change in the public interest in skincare during COVID-19 by using Google Trends.…”
Section: Introductionmentioning
confidence: 99%
“…Countries in the region instituted various levels of national restriction measures and ban on international travel starting from the mid-March 2020. 29 The number of reported confirmed COVID-19 cases in Bhutan, Maldives, Nepal, and Sri Lanka were at a low compared to other South Asian countries. These countries are either completely sea locked or sparsely populated and completely sealed their international border, which may have contributed low COVID-19 infections compared with their neighbors.…”
Section: Methodsmentioning
confidence: 96%
“…12,13 Subsequently, internet search queries also used to investigate public interest, health awareness, and mental health in the COVID-19 pandemic situation. [14][15][16] However, most of the studies so far focused on China, the United States, and other European countries. To our knowledge, there is no Infodemiology study till now have explored the association of web queries to the COVID-19 public internet and lawlessness in South Asian countries.…”
Section: Introductionmentioning
confidence: 99%